Competency based advanced training in Intellectual Disability Psychiatry: a NSW prototype. (August 2013) - Johnson, Keith; Bowden, Michael; Coyne, David; Trollor, Julian
Objective: This paper describes a competency based advanced training year in adult Intellectual Disability Psychiatry enabled through a partnership between disability and mental health sectors. This training experience could be viewed as a prototype for further specialised training schemes in Intellectual Disability Psychiatry, and has relevance for the implementation of competency based psychiatric training schemes in Australia. Conclusions: The need for a specific training curriculum in Intellectual Disability Psychiatry is outlined with reference to epidemiological evidence and human rights. The formulation of the training programme and the training experience itself is described and evaluated. Conclusions on the implications of this experience for the future competency based training schemes are drawn. Building a skilled workforce is necessary to address the significant inequalities in mental health experienced by people with intellectual and developmental disabilities. A significant initial step for this would be the development of a specialised training curriculum. Service provision for this population is scattered across many disciplines and organisations with historically little mutual cooperation. Additionally, proposed competency-based training schemes stipulate that a medical expert develops a wide skill set across multiple domains. Thus, formal cross sector collaboration is fundamental for any competency based training scheme to be feasible.